2004
DOI: 10.1111/j.1365-2141.2004.05241.x
|View full text |Cite
|
Sign up to set email alerts
|

The P303T mutation in the human factor VII (FVII) gene alters the conformational state of the enzyme and causes a severe functional deficiency

Abstract: SummaryWe report the results of in vitro expression and biochemical characterization of the naturally occurring type II mutation Pro303Thr (P303T) in the factor VII (FVII) gene. Recombinant activated mutated FVII (FVIIa303T), compared with the activated wild‐type FVII (FVIIaWT), showed reduced amidase activity toward synthetic substrates, especially when the observed reduced binding affinity for human soluble tissue factor (TF) (Kd from 4·4 nmol/l for FVIIaWT to 17·3 nmol/l for FVIIa303T) was overcome by a ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
1
4
1
Order By: Relevance
“…Q100R, F328S, and P303T changed the conformation of FVII, weakening its protease activity and diminishing affinity for TF. [32][33][34] In the present study, FVII mRNA levels and protein activity of the R53fs variant were barely detectable as a result of premature termination of translation, which would induce nonsense-mediated mRNA decay. Moreover, the R53fs truncated mutant completely lost the functional domain, including the The two variants p.Gly403Ser and p.Arg53fs in the present study were not reported in related pathogenic studies, and they were found to significantly deplete the protease activity of FVII.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Q100R, F328S, and P303T changed the conformation of FVII, weakening its protease activity and diminishing affinity for TF. [32][33][34] In the present study, FVII mRNA levels and protein activity of the R53fs variant were barely detectable as a result of premature termination of translation, which would induce nonsense-mediated mRNA decay. Moreover, the R53fs truncated mutant completely lost the functional domain, including the The two variants p.Gly403Ser and p.Arg53fs in the present study were not reported in related pathogenic studies, and they were found to significantly deplete the protease activity of FVII.…”
Section: Discussioncontrasting
confidence: 53%
“…Although the expression and secretion of this mutant protein was normal, the binding of FVII to TF was impaired, which in turn reduced its proteolytic activity. 32 The present study found that the activity of p.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Mutation detection in patient 2 revealed the 10824C>A homozygous substitution that causes the P303T defect in FVII protein. This mutation was previously detected in an Iranian patient [ 16 ]. It has been shown that residues P303, L305 and M306 are involved in tissue factor (TF) binding [ 17 ].…”
Section: Discussionmentioning
confidence: 85%
“…Protein structure analysis by X-ray crystallography has displayed that the region that contains this residue plays an important role in the interaction of EGF1 with TF [54] . In the same way, the Q100R mutation may affect the protein expression and cause defective FVIIa/TF complex formation [59] . Peyvandi et al [60] have studied Pro303Thr variant in an Iranian patient with relatively severe hemorrhage.…”
Section: Spcd G420vmentioning
confidence: 99%